RETENSI KEMAMPUAN PEMECAHAN MATEMATIKA DALAM PERSPEKTIF KETERAMPILAN ABAD 21 PADA SISWA SEKOLAH DASAR - Chrisnamurthy, Yuanita Dewi (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
ABSTRACTÂ In the 21st century it demands a mathematical literacy ability. In PISA 2012 mathematical literacy is defined as the ability of individuals to formulate, use and interpret mathematics in various contexts. Someone can be said to be able to solve a problem if able to examine a problem and be able to use their knowledge in new situations. This ability is also known as HOTS (High Order Thinking Skills) or higher order thinking skills. The purpose of this study is to determine the retention of mathematical problem solving abilities in 21st century mathematics learning. The study was conducted at SD Muhammadiyah 17 Semarang with a sample of 40th grade IV students conducted in the 2019/2020 school year. This study uses Product Moment Correlation data analysis techniques. The results showed that the retention of problem solving abilities of fourth grade students from the perspective of 21st century skills was still low.Keywords: Retention, Problem Solving Ability, Mathematics, 21st Century Skills